Manipulation of insulin signaling phenocopies evolution of a host-associated polyphenism - Meghan M. Fawcett (Nature Portfolio, 2018)
The red-shouldered soapberry bug, Jadera haematoloma, is a potential model system for developmental plasticity. Here, the authors show that the reaction norm for wing polyphenism has evolved in a recently derived ecotype and identify insulin signaling as a candidate pathway underlying this adaptive change.